In vitro multiplication of Solanum anguivi lam, Phylla.nthus amarus Schum & Thonn and Jasminum calophyllum wall - ethanomedicinal plants - M, Johnson (Ethiopian Journal of Science and Technology, 2024)
In vitro multiplication of Solanum anguivi Lam, Phyllanthus amarus Schum & Thonn. and Jasminum calophyllum Wall are medicinal plants have been achieved on Murashige and Skoog’s solid medium (1 962) augmented with 6-benzylaminopurine. The maximum numbers of shoots (Solan um anguivi, 4.8 Â± 0.17; Phyllanthus amarus, 16.3Â±0.45) are obtained in Murashige and Skoog’s medium fortified with 6-Benzyl Amino Purine (4.44 Î¼M), for Jasminum calophyllum, 4 .3 Â± 0.45 are observed in MS medium fortjfied with 6-Benzyl Amino Purine (6.66 Î¼M). The in vitro raised shoots were rooted on half strength Murashige and Skoog’s solid medium. The maximum number of roots has been induced in half strength Murashige and Skoog’s medium combinations with Naphthalene Acetic Acid (5.37 Î¼M) and !ndole-3-Acetic Acid (5.7 Î¼M) for all three plants, subsequently hardened in poly cups after that transfered to greenhouse conditions and field conditions. Nearly 65% of plants are survived in the field.